Bicyclol Attenuates Acute Liver Injury by Activating Autophagy, Anti-Oxidative and Anti-Inflammatory Capabilities in Mice - Zhao, Tian-Ming; Wang, Ya; Deng, You; Fan, Xiao-Fei; Cao, Xiao-Cang; Hou, Li-Jun; Mao, Li-Hong; Lin, Lin; Zhao, Wei; Wang, Bang-Mao; Jiang, Kui; Zhao, Jing-Wen; et al. (Frontiers in Pharmacology, 2020)
Bicyclol, a novel synthetic antihepatitis drug, has been shown to protect against liver injury via various pharmacological activities. The purpose of the current study was to further investigate the protective effect of bicyclol against carbon tetrachloride (CCl4)-induced acute liver injury (ALI) and its underlying molecular mechanism, particularly autophagic machinery, anti-oxidative and anti-inflammatory potentials. Our results found that treatment with bicyclol significantly reduced CCl4-induced hepatotoxicity by alleviating histopathological liver changes, decreasing the alanine transaminase levels, promoting autophagic flux, attenuating the expression of inflammatory cytokines and modulating oxidative markers. Furthermore, bicyclol efficiently induced the conversion of LC3 and enhanced the liver expressions of ATG7 and Beclin-1. Meanwhile, bicyclol induced the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) and p62. These protective effects may be mediated by activation of AMP-activated protein kinase and inhibition of mTOR or MAPK signaling pathways. Taken together, our study firstly suggests that bicyclol has protective potential against CCl4-induced hepatotoxicity, which might be closely associated with induction of autophagy, concomitant anti-oxidative stress and anti-inflammatory response.